Mineral Industries Of Asia And The Pacific - Introduction - Resources - E. Chin (The National Institute for Occupational Safety and Health (NIOSH), 1994)
The countries of Asia and the Pacific have large resources of diverse minerals. Australia and China have extensive mineralization that are commercially being exploited. The major minerals in Australia with known reserves adequate for both domestic demand and export markets include bauxite, clays, copper, diamond, gold, iron ore, lead, manganese, mineral sands (titanium minerals), nickel, salt, silver, tin, uranium, and zinc. China is the world leader in proven reserves of antimony, barite, magnesite, molybdenum, rare earths, titanium (ilmenite), tungsten, and vanadium. It also has about 55 billion tons of iron ore, albeit with an average grade of only 30 % to 35 % elemental iron content. With the exception of chromium and copper, China has significant resources of a wide array of minerals and metals, based on its production and/or export capability for these commodities. Additionally, India has significant resources of bauxite and mineral sands; Indonesia, bauxite, copper, nickel, and tin; Malaysia, tin and associated titanium; Mongolia, copper, fluorspar, and lead-zinc; New Caledonia, nickel; New Zealand, gold and iron sand; North Korea, magnesite; Papua New Guinea, copper, gold and mineral sands; Philippines, copper, chromite, and gold; and Sri Lanka, gemstones. Moreover, there appears to be extensive mineralization III Burma (Myanmar), Cambodia, Laos, Thailand, and Vietnam, but they have yet to be definitively delineated.